2016
DOI: 10.1128/jvi.00880-16
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking Stem-Specific Neutralizing Epitopes by Abolishing N-Linked Glycosylation Sites of Influenza Virus Hemagglutinin Proteins for Vaccine Design

Abstract: Influenza virus hemagglutinin (HA) protein consists of two components, i.e., a globular head region and a stem region that are folded within six disulfide bonds, plus several N-linked glycans that produce a homotrimeric complex structure. While N-linked glycosylation sites on the globular head are variable among different strains and different subtypes, N-linked glycosylation sites in the stem region are mostly well conserved among various influenza virus strains. Targeting highly conserved HA stem regions has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 39 publications
2
39
0
Order By: Relevance
“…While PNGase F would release N-linked glycan moieties between GlcNAc and ASN residues within a glycoprotein. It should be noted that glycosylation in insect cells is featured as terminal mannose glycans, unlike complex sialylated glycans in mammalian cells, and glycosylation is known to correlate the immunogenicity and broad-coverage protection of a glycoprotein immunogen 15, 16 . After the treatment of either Endo H or PNGase F, RBD showed no discernible decrease of molecular weight in SDS-PAGE/anti-His WB, S1 and S2 both demonstrated nearly ∼10 kDa decrease, and the intact S exhibited substantial shrinkage in molecular weight of about ∼20 kDa decrease (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While PNGase F would release N-linked glycan moieties between GlcNAc and ASN residues within a glycoprotein. It should be noted that glycosylation in insect cells is featured as terminal mannose glycans, unlike complex sialylated glycans in mammalian cells, and glycosylation is known to correlate the immunogenicity and broad-coverage protection of a glycoprotein immunogen 15, 16 . After the treatment of either Endo H or PNGase F, RBD showed no discernible decrease of molecular weight in SDS-PAGE/anti-His WB, S1 and S2 both demonstrated nearly ∼10 kDa decrease, and the intact S exhibited substantial shrinkage in molecular weight of about ∼20 kDa decrease (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies engineered glycans to expose the hidden conserved epitopes in the HA domain. For instance, one article reported that modifying glycosylation sites in the HA stem region leads to unmasked sites by N-glycans that elicit effective broadly neutralizing antibodies [80]. Such studies confirmed the potential role of engineering in changing the immunogenicity of antigens and exposing conserved sites, which are the key to induce broadly neutralizing antibodies [76,81,82].…”
Section: Recent Advances In Anti-ha Antibodiesmentioning
confidence: 88%
“…For example, through identification of conserved glycosites in the stem region of the influenza strain H5, novel vaccine candidates were created. By mutation of certain conserved glycosites, it was possible to make a vaccine resulting in a refocused B‐cell response with improved neutralization of homologous, heterologous, and heterosubtypic viruses . While protection against challenge with lethal homologous virus was substantially improved, high mortality was still observed when challenged with a virus of a different subtype, showing that further vaccine optimization is needed .…”
Section: Practical Implications Of Glycosite Discovery In Virologymentioning
confidence: 99%
“…By mutation of certain conserved glycosites, it was possible to make a vaccine resulting in a refocused B‐cell response with improved neutralization of homologous, heterologous, and heterosubtypic viruses . While protection against challenge with lethal homologous virus was substantially improved, high mortality was still observed when challenged with a virus of a different subtype, showing that further vaccine optimization is needed . Modulating glycan density on immunogens has been one of the approaches utilized in vaccine design .…”
Section: Practical Implications Of Glycosite Discovery In Virologymentioning
confidence: 99%